An Analysis and Design of Network Security Using Firewall at the Library and Archives Services of Bengkulu province - Defri Riyanto; Khairil Khairil; Eko Prasetiyo Rohmawan (Jurnal Komputer, Informasi dan Teknologi, 2021)
This study is based on the problems that are often encountered in the research location, namely how to secure the inlislite server by designing network security using Packet Filter Firewall of IPtables. The purpose of this study is to optimize the data security of the inlislite system in the Library and Archives Service of Bengkulu Province. The method used is the Network Development Life Cycle (NDLC) method, a cycle of network design stages that can guide a network design, which depends on the size of the project to be implemented and the purpose of the project. By testing a Denial of Service (DoS) attack against inlislite using hping3 on linux, the inlislite website can no longer be accessed. Therefore, the author designed a new system to secure the inlislite server from unwanted attacks using the IPTables firewall filter then it can become a firewall that will ward off Distributed Denial of Service and Denial of Service attacks on inlislite servers. From the results of research and testing that has been carried out, the IPTables firewall is very good for securing servers in the Library and Archives Service of Bengkulu Province and applying more rules to clients in terms of internet use.